An Analysis Of The Relationship Between National Economic Productivity And Income Inequality (Journal of Pharmaceutical Negative Results, 2023)
The objective of this inquiry is to determine how economic productivity and income disparity are related. Previous studies on the subject have produced mixed findings, with some studies finding a positive correlation and others finding a negative explanation for how income inequality affects economic performance. Both a single and numerous instances of linear regression analysis are employed in this study to ascertain the relationship between the two variables. Models 4 through 6 find a poor link between income inequality and economic growth, in contrast. Particular focus was given to the study's dummy variable, which represented a country's developmental stage.